Rondas infantiles y la comunicación oral en niños de la Institución Educativa Inicial N° 728, Caballococha 2025 - Licla Achulla, Saturnina Victoria (2025)
The main objective of this study was to determine the relationship between nursery rhymes and oral communication in children at the Initial Educational Institution No. 728, Caballococha 2025. The research was conducted using a quantitative approach, with a non-experimental, correlational methodological design. The sample consisted of 100 students from said institution. Data collection was based on direct observation using a specially designed guide validated by experts in education and psychology. The results of the Spearman correlation test, with a coefficient of 0.512, indicate a moderate and positive relationship between nursery rhymes and oral communication. Furthermore, the two-tailed Sig. value of 0.007 is less than 0.05, which allowed us to reject the null hypothesis (H0) and confirm a significant relationship between nursery rhymes and the development of oral communication. This finding supports the hypothesis that nursery rhymes have a positive impact on improving oral communication, demonstrating a statistically significant relationship.